The Role of Serum Neutrophil Gelatinase-associated Lipocalin in the Early Diagnosis of Nephropathy in Patients with Acute Alcohol Poisoning - Demidchik, L.; Klyuyev , D.; Muravlyova, L.; Molotov-Luchanskiy , V.; Bakirova , R. (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: In our study, we assessed the possibility of using the serum neutrophil gelatinase-associated lipocalin (NGAL) for the early detection of kidney damage in patients with acute alcohol poisoning (AAP). METHODS: The study included 89 patients and 30 healthy donors. All participants in the study were mostly represented by men (90%) aged between 20 and 40 years. The influence of alcohol poisoning severity was also taken into account in the study. The Human NGAL ELISA Kit was used for the quantitative detection of serum NGAL. We also evaluated the main laboratory indicators of kidney functions, including eGFR (calculated according to serum creatinine). RESULTS: We did not find a correlation between blood alcohol concentration and serum NGAL level; also, alcohol poisoning severity did not affect the NGAL values. The results of our study showed the possibility of using the serum NGAL in patients with AAP to detect the preclinical stage of reduced renal function, until the moment when it can be diagnosed with using only serum creatinine. CONCLUSION: We propose to consider an increase in eGFR together with an increase in serum NGAL in this group of patients as a stage, preceding nephropathy, even in the absence of clinical and laboratory signs of impaired renal function.